Implikasi Sejarah Transmisi Al-Qur’an Terhadap kerja Orientalis - Muhammad Mabrur Barizi (Millati: Journal of Islamic Studies and Humanities, 2017)
This article attempts to explore and trace the history of the Qur'an especially regarding the transmission of the Qur'an in the perspective of insider (Muslim) and outsider (orientalist). Both of these perspectives need to be studied deeply and proportionally in order to the horizon of the study of the Qur'an continue to be dynamic and progressive, although sometimes the study conducted by the outsider is not in line with the views of Muslim scholars. It can be seen from the thesis proposed by A. Jeffery and John Wansbrough. From the results of the study it could be concluded that both A. Jeffery and John Wansbrough read the Qur'an by the same method applied to the bible (bible criticism), such as historical criticism, source criticism, form criticism and textual criticism, this kind of perspective would have implications against the text of the Qur'an as plain text. Both A. Jeffery and John Wansbrough argued that they were not convinced of the existence of the Qur'anic set on the basis of the absence of the Prophet's attempt to gather until he died. While other orientalists like Angelika Neuwirth had a different perspective regarding the writing and codification of the Qur'an. She argued that since the time of the Prophet already contained the writing of the Qur'an. The differences of view among the orientalists became a proof that the study of the Qur’an among outsiders was not always negative and polemic.